Use EVA to Measure and Manage Shareholder Value in a Chinese Listed Corporation ------Ningbo Bird Corporation - Jiang, Feng (2007)
This dissertation detailedly introduces how to calculate EVA and how to use EVA to value shareholder wealth in a Chinese listed corporation. It is involved with the calculation of NOPAT and capital employed adjusted from financial report, the estimation of the discount rate, the projection of company's future performance and the final valuation of shareholder wealth. Besides this, this paper demonstrates the validity and reliability of EVA as a measure of shareholder value in Bird through Pearson's correlation test model. In addition, this paper validates the theoretical consistency of EVA and DCF as a measure of shareholder value in Bird. Incidentally, this paper examines the efficiency of Chinese stock market through the comparison between external market value and internal intrinsic value of shareholders in Bird and finds that the stock market in China is highly volatile and speculative. Finally, the study discloses that Bird is a value destroyed corporation and the most effective and direct measure for Bird top management is to sell the company as quickly as possible.